Faktor Risiko Penularan Malaria Di Jawa Barat (Kajian Epidemiologi Tentang Vektor, Parasit Plasmodium, dan Lingkungan Sebagai Faktor Risiko Kesakitan Malaria) - Lukman Hakim (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Since the territory is divided with the province of Banten, in West Java there are five regencies that defined as malaria endemic area, there are Ciamis, Tasikmalaya, Garut, Cianjur and Sukabumi. Sufferer, concentrated in southern coastal areas (Indonesian Ocean) starting from the beach of Kalipucang at Ciamis up to coast of Cikakak at Sukabumi which borders the province of Banten and also mountain and plantations areas. Malaria morbidity incidence risk factors is differ in each of these endemic areas. In general is the presence of malaria patients without symptoms who can be a source of infection thatso difficult to know its existence. Still the number of standing water that can become mosquito breeding places of Anopheles spp, such as fish pond, small puddle on the riverside, shrimp pond, mangrove forests that potentially at the beginning of the rainy season, thefields during rice that potential when the rice growing and the river that potential in the dry season. The existence of high population mobility and also the number of vegetation in the surrounding residential population and the existence of cattle are placed close to settlements.